دلالة الزمان والمكان في قصيدة الجبل لابن خفاجة الأندلسي - علي عامر د. فاطمة أرحومة (Aljameai)
المستخلص: تركز هذه الدراسة على دلالة الزمان والمكان في قصيدة الجبل لابن خفاجة الأندلسي من خلال توظيف القراءة التأويلية لدلالة الزمان والمكان ومحاولة استنطاق النص من خلال توظيف العديد من المعاني والدلالات وإعادة بناء النص وفق تصور القارئ بوصفه المنتج الذي يقدم قراءة جديدة للنص وفي سبيل تحقيق ذلك تم توظيف الجانب الاحصائي لإعطاء دلالة على التصور الجديد فمن وصف الجبل بنينا صورة جيدة تدل على الوطن فالجبل مجرد اسقاط على الوطن الذي غادره الشاعر وقد نجح الشاعر في وصف الجبل للدلالة على الوطن الراسخ في قلب كل انسان يحب الوطن وينتمي إليه. Abstract This study focuses on the significance of time and place in the poem “The Mountain” by Ibn Khafaja Al-Andalusi by employing an interpretive reading of the significance of time and place and attempting to interrogate the text by employing many meanings and connotations, reconstructing the text and searching for other spaces to which the text takes us, according to the reader’s perception as the product that provides a reading. New to the text, and in order to achieve this, the statistical aspect was employed to give an indication of the new perception, from the description of the mountain, we built a good picture that indicates the homeland. The mountain is merely a projection of the homeland that the poet left. The poet succeeded in describing the mountain to indicate the homeland that is firmly established in the heart of every person who loves the homeland and belongs to it.